Inflation Forecasting with Inflation Sentiment Indicators - Roland Döhrn; Christoph M. Schmidt; Tobias Zimmermann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
In this paper we argue that future inflation in an economy depends on the way people perceive current inflation, their inflation sentiment. We construct some simple measures of inflation sentiment which capture whether price acceleration is shared by many components of the CPI basket. In a comparative analysis of the forecasting power of the different inflation indicators for the US and Germany, we demonstrate that our inflation sentiment indicators improve forecast accuracy in comparison to a standard Phillips curve approach. Because the forecast performance is particularly good for longer horizons, we also compare our indicators to traditional measures of core inflation. Here, the sentiment indicators outperform the weighted median and show a similar forecasting power as a trimmed mean. Thus, they offer a convincing alternative to traditional core inflation measures.
Keywords: E30; E31; E37; C53; 330; Inflation forecasting; monetary policy; Inflation; Prognoseverfahren; Inflationserwartung; Wahrnehmung; Schätzung; USA; Deutschland